2019
DOI: 10.1186/s40104-019-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fiber content and different fiber-rich ingredients on endogenous loss of fat and fatty acids in growing pigs

Abstract: Background Determination of the endogenous loss of fat (ELF) is used to adjust for the estimation of true total tract digestibility (TTTD) of fat in diets and ingredients. Any factor which affected ELF may further affect the digestibility of fat, including sources and concentrations of fat and fiber in the diet. There are some reports of determining the ELF using regression methods based on different levels of fat intake, while reports on effects of dietary fiber content and different fiber-rich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Instead of feeding traditional diets based on natural ingredients (corn, barley, soybean meal, canola meal), cornstarch and soy protein isolate containing lower fiber content were formulated in the present diets. Previous studies reported that greater dietary fiber content resulted in increasing endogenous fat excretion [2,6,7]. In addition, purified ingredients with high digestibility may decrease endogenous fat excretion [22,23].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Instead of feeding traditional diets based on natural ingredients (corn, barley, soybean meal, canola meal), cornstarch and soy protein isolate containing lower fiber content were formulated in the present diets. Previous studies reported that greater dietary fiber content resulted in increasing endogenous fat excretion [2,6,7]. In addition, purified ingredients with high digestibility may decrease endogenous fat excretion [22,23].…”
Section: Discussionmentioning
confidence: 97%
“…1 Sixteen observations in each equation. 2 Calculated from regression equation y = ax + b, where x = dietary fat intake (g/kg of DMI), y = apparently digested fat (g/kg of DMI) of total intestinal tract. 3 Values for endogenous loss of individual fatty acid in pigs fed palm oil, soybean oil, flaxseed oil or rapeseed oil were compared, but no differences were observed (p > 0.10 and standard error of the means = 2.57).…”
Section: Elfa Obtained By the Regression Methodsmentioning
confidence: 99%
See 3 more Smart Citations